Confirming Dividend Changes and the Non-Monotonic Investor Revision of Earnings Persistence - Müller, Christian. (Quantitatives Controlling, 2014)
The stylized facts that firms pay and investors react to dividends disregard dividend neutrality. Taking on the perspective that informational asymmetries are the central determinant for dividend value relevance, Christian Müller assumes that firm’s dividend decision conveys useful information to investors. He shows that investors use dividend changes to revise their a priori expectations about the persistence of a current earnings change. While his theoretical and empirical analyses generally imply that dividend changes constitute informative, but imperfect information signals, he further identifies situations in which they are substantial to investors. Christian Müller’s research comprehensively examines the informational role of dividend policy and provides new insights to the corresponding Bayesian investor learning process.   Contents n  Dividend Irrelevance and Competing Dividend Theories n  Incremental Importance of Dividend Changes in Signaling Earnings Persistence – Theoretical and Empirical Analysis n  Measuring A Priori Investor Knowledge about Earnings Persistence   Target Groups ·        Academics and students in the fields of finance and accounting ·        Corporate managers, investment professionals, and anyone interested in the implications of payout policy   The Author Dr. Christian Müller received his doctoral degree from the University of Cologne under the supervision of Prof. Dr. Carsten Homburg (Department of Business Administration and Management Accounting).  .